2016
DOI: 10.14260/jemds/2016/1289
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Open Phalangeal and Metacarpal Fractures Treated With External Fixation

Abstract: MATERIALS AND METHODSThe common age group affected was 21-30 years with mean age being 35.5 years (13-60 years). Most of the injuries were caused by industrial accidents (57.6%). In 34.6% of cases, the dominant hand was involved. All patients were treated with wound debridement, external fixation and early mobilisation of the fingers. The follow-up period ranged between 2.3 -8.2 years (mean 4.4 years). Complications occurred in ten fractures. Loosening of the pin (6) was the most common complication. Except tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…When complications were compared statistically among the groups using chi square test, it was found to be statistically insignificant. Similar results were found by Kishore Kannan et al [14] in their study. Rakesh Gupta et al [1] stated that a total of 22 complications were observed in10 patients out of a total of 31.…”
Section: Complicationssupporting
confidence: 91%
See 2 more Smart Citations
“…When complications were compared statistically among the groups using chi square test, it was found to be statistically insignificant. Similar results were found by Kishore Kannan et al [14] in their study. Rakesh Gupta et al [1] stated that a total of 22 complications were observed in10 patients out of a total of 31.…”
Section: Complicationssupporting
confidence: 91%
“…Kirschner pins may loosen and may distract the fracture fragments. Furthermore, pin tract infections may develop secondary to skin irritation or loosening and pin protrusion may make therapy and splintage awkward 5 .…”
Section: Kirschner Wirementioning
confidence: 99%
See 1 more Smart Citation